Lipid accumulation patterns and role of different fatty acid types towards mitigating salinity fluctuations in Chlorella vulgaris - Teh, Kit Yinn (Sci Rep, 2021)
Mangrove-dwelling microalgae are well adapted to frequent encounters of salinity fluctuations across their various growth phases but are lesser studied. The current study explored the adaptive changes (in terms of biomass, oil content and fatty acid composition) of mangrove-isolated C. vulgaris UMT-M1 cultured under different salinity levels (5, 10, 15, 20, 30 ppt). The highest total oil content was recorded in cultures at 15 ppt salinity (63.5% of dry weight) with uncompromised biomass productivity, thus highlighting the ‘trigger-threshold’ for oil accumulation in C. vulgaris UMT-M1. Subsequently, C. vulgaris UMT-M1 was further assessed across different growth phases under 15 ppt. The various short, medium and long-chain fatty acids (particularly C20:0), coupled with a high level of C18:3n3 PUFA reported at early exponential phase represents their physiological importance during rapid cell growth. Accumulation of C18:1 and C18:2 at stationary growth phase across all salinities was seen as cells accumulating substrate for C18:3n3 should the cells anticipate a move from stationary phase into new growth phase. This study sheds some light on the possibility of ‘triggered’ oil accumulation with uninterrupted growth and the participation of various fatty acid types upon salinity mitigation in a mangrove-dwelling microalgae.